Assessment methods on serious games. Issue 4 (27th September 2019) - Oliveira, Carlos; Pimentel, Ulrick
Digital games have conquered a growing space in the lives of children, adolescents and adults. In this perspective, the use of this resource has shown to be an important strategy that facilitates the learning process. This research is a literature review on the use of serious games in teaching, which shows the characteristics of these games, the benefits and possible harms that this resource can produce, in addition to the possible methods of evaluating the effectiveness of this resource in teaching. The results point out that serious games have significant potential as a tool for instruction. However, their effectiveness in terms of learning outcomes is still poorly studied, mainly due to the complexity involved in evaluating intangible measures.